Injectable Hydrogel with Slow Degradability Composed of Gelatin and Hyaluronic Acid Cross-Linked by Schiff’s Base Formation - Hozumi, Takuro; Kageyama, Tatsuto; Ohta, Seiichi; Fukuda, Junji; Ito, Taichi (Biomacromolecules, 2018)
We developed an injectable gelatin/hyaluronic acid hydrogel with slow degradability, which consisted of carbohydrazide-modified gelatin (Gel-CDH) and hyaluronic acid monoaldehyde (HA-mCHO). Gel-CDH/HA-mCHO hydrogels were degraded much more slowly in phosphate-buffered saline than the other Schiff’s base cross-linked gelatin/hyaluronic acid hydrogels that were comprised of native gelatin, adipic acid dihydrazide-modified gelatin, or hyaluronic acid dialdehyde because of stable Schiff’s base formation between aldehyde and carbohydrazide groups, and suppression of ring-opening oxidation by monoaldehyde modification. This prolonged degradation would be suitable for inducing angiogenesis. Therefore, the Gel-CDH/HA-mCHO hydrogels were sufficiently stable during the angiogenesis process. In addition, the hydrogel had a pore size of 15–55 μm and a shear storage modulus of 0.1–1 kPa, which were appropriate for scaffold application. Ex vivo rat aortic-ring assay demonstrated the concentration dependency of microvascular extension in the Gel-CDH/HA-mCHO hydrogel. These results demonstrated the potential usefulness of Gel-CDH/HA-mCHO hydrogel for tissue-engineering scaffolds.